Extraction and spectrophotometric quantification of total polyphenolic content in onion. - Jankulovska, M S.., Sokolovska, V., Velkoska-Markovska, L., Bogevska, Z., Karakasova, Lj., Manasievska, S., Miskovska-Milevska, E., Babanovska-Milenkovska, F., Markoski, M. (Agriculture and Forestry, 2023)
Consumption of food rich in polyphenols such as fruits and vegetables is of great importance, because it contributes to the prevention of various diseases. Polyphenols are a group of bioactive compounds which can play significant role in preventing various health related problems. One of the richest sources of polyphenols in the human diet is the onion (Allium cepa L.). The main objective of the present investigation is quantification of total polyphenolic content (TPC) in the Macedonian local population of onion. A various organic solvents were tested (methanol, ethanol, ethyl acetate and acetone) and their different concentrations (20, 40, 60 and 80%) in order to establish optimum solvent concentration for extraction of polyphenols from onion. Time for extraction was another important parameter which was examined as well. TPC was determined by UV-Vis spectroscopy in accordance with the Folin–Ciocâlteu assay, using gallic acid as a reference standard. The results were expressed as mg gallic acid equivalents GAE/100 g fresh onion. The highest polyphenolic level was determined in 60% methanol (38.81±0.39 mg GAE/100 g), while lower total polyphenolic content was found in the ethyl acetate extracts (27.10±0.35 mg GAE/100 g). Regarding the time for extraction, the highest content of total polyphenols in onion was obtained during extraction of 120 minutes (37.95±0.63 mg GAE/100 g)
Keywords: UV-Vis spectroscopy, onion, extraction, gallic acid, total polyphenolic content (TPC).